Pengaruh Work-Family Conflict dan Family-Work Conflict terhadap Fear of Success pada Pegawai Negeri Sipil Perempuan - Friska Pontoria (KOLONI, 2026)
Horner explained that the fear of success arises from a fundamental fear of losing femininity due to the negative consequences associated with women's achievements in fields traditionally dominated by men, including social disapproval and rejection. This fear is rooted in societal expectations (Ivers & Downes, 2012; Moulik & Ray, 2023). Social norms often portray women as feminine, obedient, devoted, passive, responsible for household duties, and accountable for others, leading many women to fear violating these norms as a consequence of achieving success (Dewi, 2017). Furthermore, patriarchal cultural values that associate women primarily with domestic responsibilities reinforce social sanctions against women who pursue career advancement. Netemeyer et al. (1996) conceptualized Work-Family Conflict in two primary directions: work interfering with family (WFC) and family interfering with work (FWC). This study aimed to examine the influence of Work-Family Conflict and Family-Work Conflict on Fear of Success among female employees. A quantitative research design was employed, and data were collected using a nonprobability sampling approach, specifically purposive sampling, involving 311 participants. The findings revealed that Work-Family Conflict had a positive and significant effect on Fear of Success, with a path coefficient of 0.321, a T-statistic of 9.435 (> 1.96), and a P-value of 0.000 (< 0.05). Similarly, Family-Work Conflict also had a positive and significant effect on Fear of Success, with a path coefficient of 0.242, a T-statistic of 6.843 (> 1.96), and a P-value of 0.000 (< 0.05).